Rut Performance of In Situ Warm Mix Asphalt Overlays with Evotherm 3G in North Dakota - Mahdi Rezapour; Shaun S. Wulff (Journal of Engineering)
As warm mix asphalt (WMA) pavements afford compaction at temperatures several dozen degrees lower than hot mix asphalt (HMA), the rate of cooling drops dramatically allowing paving to continue into colder weather. For this study, field samples from the Valley City project were collected after being in service (aged) for three years. The historical weather data during study period, 2011-2014, indicates that the temperature in Valley City dropped up to −34°C in winter. Prior studies have noted the importance of studying the performance of asphalt in different environmental conditions, and with different additives. Therefore, this study was set forward to study rutting resistant of field WMA in one of the coldest regions in the US, which used Evotherm 3G as an additive. The research aimed to compare aged WMA rutting resistance, including Evotherm 3G, to that when the specimens were newly constructed. The Asphalt Pavement Analyzer (APA) was used to compare the rutting resistances of WMA and the control HMA. The results indicated that aged samples were more rut resistant than nonaged samples under wet and dry testing conditions. Also under wet and dry testing conditions, aged WMA samples exhibited lower rutting resistance than aged HMA samples. No interaction effects of aging and Evotherm 3G were found on the rutting resistance of asphalt. Addressing the issue of binder aging and its effects on the overall rut performance of pavements gives further insight into the utility of WMA overlays in cold weather regions such as North Dakota.